The Migration from Analog to Digital Television - Choirul Ulil Albab; Muhammad Noor Hidayat; Muhamad Hasan Basori (Jurnal Audience: Jurnal Ilmu Komunikasi, 2022)
This study aims to see the effect of information exposure in the mass media and the level of public knowledge about digital television on people's decision making to adopt digital television. Digitization of television in Indonesia has been prepared more than 12 years ago. In 2009 Indonesia had prepared a framework for the implementation of a digital broadcasting system which was later in 2010. However, the migration process for digital television in Indonesia did not go well because of the conflict of interest of private television and regulations that were not yet strong. The theory of diffusion of innovation from Everett M. Rogers is used to provide an explanation of the pattern of adoption of new technologies in society. This quantitative study will measure the effect of exposure to digital television information and the level of public knowledge as independent variables and decision-making to adopt technology as the dependent variable. In this study, 120 respondents were selected based on the slovin formula with the number of families in Central Java as the population.. As a result, the effect of these variables is not significant. Digital television migration policy is a priority policy with authority innovation desicions. It stated in the UU Cipta Kerja which states that Indonesia must immediately switch analogue switched off a maximum of two years. So that the readiness and knowledge of the community will not affect the decision to adopt digital television or not.Keywords: Diffusion of Innovation; Digital Television Migration; Public Readiness